Gorska ranljiva območja - primer Triglavskega narodnega parka - Rejec Brancelj, Irena (Geographica Slovenica, 2000)
The human influence on the vulnerable mountain areas was studied in the Triglav national park. There were three activites of the main economic importance in the past executed in this area: ironworks, mountain pasturing and forestry. Nowadays the human´s influence is much more variegated. Dwelling of the same in the central part of the park is mostly of the season character and connected with the tourism and recreation as well as with holidays-spending. Local pollution is the result of the human activities, exploiting the natural sources, of local intensive traffic and of permanent and perodic settlement.
Keywords: ecology; ekologija; varstvo okolja; environmental protection; ekološko ravnotežje; sonaravni razvoj; sustainable development; trajnostni razvoj; narodni parki; Triglav National Park; Triglavski narodni park; Slovenia; Slovenija